Education Politics and Policy: Emerging Institutions, Interests, and Ideas - Galey, Sarah (Policy studies journal, 2015)
The article reviews the most recent research on K–12 education policy and politics in the United States. I begin by exploring current reform trends and emerging institutional arrangements governing contemporary U.S. school systems in relation to patterns of increasing federal and state involvement in educational policy arenas. I then examine and synthesize studies from four key areas of educational policy research—accountability and teacher evaluation, market‐based reforms, educational research utilization, and local and state capacity building. I conclude with an overview of gaps in the literature and suggestions for future research.